2011
DOI: 10.1097/psy.0b013e31821db79a
|View full text |Cite
|
Sign up to set email alerts
|

Depressed Mood and Flow-Mediated Dilation

Abstract: Objective This systematic and quantitative review evaluates the literature on associations between depressed mood and flow-mediated dilation (FMD), a measure of endothelial function, in adults. Methods Published English-language articles (through December 2010) were identified from literature searches, assessed for data extraction, and evaluated for quality. Results The literature includes cross-sectional (n = 9) and retrospective examinations (n = 3) of how FMD correlates with clinical or subclinical depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 53 publications
2
44
2
Order By: Relevance
“…(6) Patients with depression evidence impaired flow-mediated vasodilation, directly demonstrating impaired vascular function and a link to increased risk of future cardiovascular disease. (7) Together, these results suggest that vascular dysfunction may be an important underlying aspect of depression.…”
Section: Introductionmentioning
confidence: 82%
“…(6) Patients with depression evidence impaired flow-mediated vasodilation, directly demonstrating impaired vascular function and a link to increased risk of future cardiovascular disease. (7) Together, these results suggest that vascular dysfunction may be an important underlying aspect of depression.…”
Section: Introductionmentioning
confidence: 82%
“…Wider retinal arteriolar caliber is a sign of impaired autoregulation (57) and has been shown to be associated with reduced flicker-induced vasodilation (58). Notably, endothelial dysfunction is seen in individuals with depression and anxiety (5, 56, 59). For example, a meta-analysis reported a statistically significant overall correlation of 0.19 between depressed mood and reduced flow-mediated dilation in adults (59).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, endothelial dysfunction is seen in individuals with depression and anxiety (5, 56, 59). For example, a meta-analysis reported a statistically significant overall correlation of 0.19 between depressed mood and reduced flow-mediated dilation in adults (59). Recent studies of children and adolescents have also shown an association between depression and anxiety and impaired endothelial function assessed using the EndoPAT device (5456).…”
Section: Discussionmentioning
confidence: 99%
“…[1516] According to a new meta-analysis, including studies on healthy subjects and also patients with CVD, mood disorders have been associated with endothelial dysfunction measured by FMD (an early marker of CVD)[17] Also, using antidepressant medication in patients with CVD who were depressed was associated with improved FMD[1819] However, the responsible mechanisms for this association are not clear yet. [15] The effects of psychological factors on the immune system have been considered and reviewed for long.…”
Section: Discussionmentioning
confidence: 99%